Pengaruh Model Pembelajaran Arias dengan Selingan Ice Breaker terhadap Hasil Belajar IPA - ni made pratiwi satriani; Ketut Pudjawan; i made suarjana (Universitas Pendidikan Ganesha, 2018)
This study is aimed at finding out the significant difference of natural science learning result between group of students who took the ARIAS learning with an ice breaker model and group of students who took conventional learning on the fifth grade students of elementary school in Cluster II Sukasada subdiscrit in academic year of 2017/2018.This was a type of quasi experimental study,using post test only non-equivalent control group design. The population of this study was students of the fifth grade in Cluster II Sukasada subdiscrit in academic year of 2017/2018.The samples of this study were the fifth grade students of SDN 1 Pegayaman with consisted of 32 students as the experiment group and SDN 3 Gitgit with consisted of 30 students as the control group. The sampling technique used in this research was the random sampling technique. The collected data in this research were analyzed by using test method with objective test instrument. The obtained data was then analyzed by using descriptive statistic and inferential (t-test). Based on the mean calculations of natural science learning result of the group of students who took ARIAS learning with an ice breaker that is 24,03 better than who took conventional learning that is 14,30. That means, there is significant difference on the natural science learning result between group ofstudents who took the ARIAS learning with an ice breaker model and group of the students who took conventional learning. This indicates that ARIAS learning with ice breaker take effect toward natural science learning result of the fifth grade elementary school students in Cluster II Sukasada subdiscrit in academic year of 2017/2018.